Rotor Fault Detection and Isolation in Aerial Vehicles with Dozens of Rotors - Gandhi, Neeraj; Xu, Jiawei; Saldaña, David; Phan, Linh Thi Xuan (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XXI Simpósio Latino Americano de Robótica, 2024)
Aerial vehicles with dozens of rotors are becoming increasingly common in important applications such as transportation and construction. One challenge with building such a system is to ensure that the system is robust against faults: as the number of rotors increases, the likelihood of a rotor failing during operation also increases; despite the spare thrust capacity provided by the redundant rotors, a rotor fault can significantly impact the motion and safety of the system.This paper presents an efficient fault detection and isolation (FDI) method for aerial vehicles with a large number of rotors. Our approach relies on two key insights: First, the effect of a faulty rotor directly affects the tracking error in roll and in pitch. This property can be used to order our faulty rotor search space. Second, the error in either roll or pitch is related to both the distance from the (relevant) axis and the severity of a fault. With these observations, we can use probe faults to isolate faulty rotors. Evaluation results show that our technique can efficiently detect and isolate faults in multi-rotor aerial vehicles with up to 64 rotors (8× more rotors than in existing FDI work), and that it can help improve robustness. To the best of our knowledge, our FDI method is the first that scales to several dozens of rotors.